Confucian values and Chinese geopolitical discourse on terrorism: China's reappraisal of international security politics. Issue 3 (4th May 2019) - An, Ning
ABSTRACT: This paper studies articles about terrorism in the representative Chinese newspaper People's Daily in order to analyze how traditional Chinese political culture, in particular Confucianism, permeates contemporary Chinese geopolitical discourse. Specific attention is paid to articles on terrorism and the U.S. "war on terror." The author argues that, instead of interpreting terrorist actions and U.S. counter-terrorism politics as binary opposites, using a lens of a Confucianism-style morality, the Chinese newspaper observes connections between them. The author considers how these discourses affect China's perception of itself in the realm of international security politics. The representative Chinese newspaper articles on terrorism, in addition to China's repositioning on the global stage, reveal a geopolitical fault-line with strong moral undertones. The paper sheds light on the historic and often implicit political impact of Confucianism within present day Chinese geopolitical discourse and practice.